LEARNING NEEDS OF THE STUDENTS THROUGH HOMESCHOOLING - Faisal Faisal; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2019)
Education that is prepared by the government, whatever its form of education, is basically held to free people from the various problems of life that surround them. The focus of this research is to find out: (1) How is the implementation of the homeschooling community in meeting the learning needs of children with special needs? in meeting the learning needs of children with special needs? This research uses a qualitative approach. Research data collection using in-depth interviews, participant observation, documentation. Research subjects include: managers of homeschooling institutions, educators / tutors and homeschooling families. To guarantee the trustworthiness / truth of the results of qualitative research, this study was carried out for two months, while the steps in data analysis included: data reduction, data display, data verification and conclusions The results showed that the implementation of homeschooling in meeting the learning needs of children with special needs in Imanuel Surabaya homeschooling in the implementation and learning process is based on the needs of different children, especially on children with special needs that are tailored to the level of ability, barriers experienced and the character of communication that develops aspects of talent and interests so that their educational needs can be met